THE MEANING OF THE EXPERIENCE OF NOT BREAST-FEEDING RELATED TO BREAST ISSUES - Liliany da Silva Quirino; Joseph Dimas de Oliveira; Maria de Fátima Esmeraldo Ramos de Figueiredo; Glauberto da Silva Quirino (Universidade Federal do Paraná, 2011)
The objective of this study was to relate the experience of women in the practice of maternal breastfeeding, to describe the feelings experienced by those who do not breastfeed their babies, and study the meaning of not breastfeeding. The study is descriptive with a qualitative approach, and was carried out among Family Health teams in Juazeiro in North Ceará, with the participation of five women who were not breastfeeding due to breast issues. A questionnaire and semi-structured interview using thematic content analysis were used to collect data. Three categories emerged: The experience of women in the practice of breast-feeding and Feelings experienced by the women . The feelings noted by the participants and their meanings in not breast-feeding were sadness, impotence, pain, relief from obligation, and calming. It is considered that breastfeeding is a process of adaptation, teaching and learning and that it is strongly influenced by ideological, personal and socio-psycho-cultural factors: and that this demands of the health care professional both understanding and situation-specific training.